A history of modern translation knowledge : sources, concepts, effects - Hulst, Lieven d'; Gambier, Yves, 1949- (Benjamins translation library, 2018)
"A History of Modern Translation Knowledge is the first attempt to map the coming into being of modern thinking about translation. It breaks with the well-established tradition of viewing history through the reductive lens of schools, theories, turns or interdisciplinary exchanges. It also challenges the artificial distinction between past and present and it sustains that the latter's historical roots go back far beyond the 1970s. Translation Studies is but part of a broader set of discourses on translation we propose to label "translation knowledge". This book concentrates on seven processes that make up the history of modern translation knowledge: generating, mapping, internationalising, historicising, analysing, disseminating and applying knowledge. All processes are covered by 58 domain experts and allocated over 55 chapters, with cross-references. This book is indispensable reading for advanced Master- and PhD-students in Translation Studies who need background information on the history of their field, with relevance for Europe, the Americas and large parts of Asia. It will also interest students and scholars working in cultural and social history"--